Regional-scale environmental drivers of highly endemic temperate fish communities located within a climate change hotspot - Galaiduk, R.; Halford, A.; Radford, B.; Moore, C.; Harvey, Euan (Blackwell Science Ltd, 2017)
Â© 2017 John Wiley & Sons Ltd Aim: We used modelled environmental data to identify important drivers of bioregional patterns of demersal fish assemblages characterized by a high proportion of endemic species. Location: Of 1,600Â km of coastal marine environment in south-western Australia. Methods: We compiled data from 1090 stereo-BRUVs samples; a total of ~55,000 individuals belonging to 219 demersal fish species. Multivariate Regression Trees and Distance-based Linear Models distinguished which biological and/or environmental variables, amongst an initial set of 49, were most correlated to observed patterns of demersal fish assemblage structure. Indicator species analysis identified fish species most representative of the assemblage types. Results: The most parsimonious model (constrained by five benthic variables and one spatial variable) explained 42% of the variation in spatial patterns of fish community structure. Canopy-forming seaweeds were the major benthic drivers, and, when found on structurally complex hard habitat, supported the highest diversity of species after sites dominated by hard coral cover. Indicator species analysis revealed that 28 of 35 significant species for this habitat type were endemics with fish assemblages associated with these habitats often spatially restricted to tens of kilometres. Main conclusions: Demersal fish assemblage composition and biogeographical ranges in south-western Australia are strongly influenced by the presence of canopy-forming macroalgae. Canopy-dominated habitats have already been subject to catastrophic temperature-related die-offs in the northern part of this study, indicating its vulnerability to temperature-driven climate change. These results highlight not only the crucial role of this habitat in supporting endemic fish communities in the region, and the tenuous nature of their existence, but also the challenges facing marine managers who, unable to manipulate the influence of climate change variables, can only focus on alleviating stresses operating on local scales.